Community Perceptions of Person-Centered Maternity Care in Migori County, Kenya - Osamuedeme Odiase; Beryl Akinyi; Joyceline Kinyua; Patience Afulani; Patience Afulani (Frontiers Media S.A., 2021)
Background: Community perceptions of quality of maternal healthcare services-including Person-centered maternity care (PCMC)-influences the health-seeking behavior of women. Yet few studies have examined this quantitatively. This study aims to examine community perceptions of PCMC and its associated factors.Materials and Methods: We used data from a survey on community perceptions of PCMC in Migori County, Kenya conducted in August 2016. Community members were relatives or friends of women aged 15 to 49 years who gave birth in the 9 wk preceding the survey (N = 198). PCMC was measured using a 30-item scale with three sub-scales for dignity and respect, communication and autonomy, and supportive care. PCMC scores were standardized to range from 0 to 100, with higher scores indicative of higher PCMC. Descriptive, bivariate, and multivariate analyses were performed in STATA (version 14).Results: The average total PCMC score was 62 (SD = 15.7), with scores of 74, 63, and 53 for dignity and respect, supportive care, and communication and autonomy, respectively. Controlling for other factors, respondents who were employed and literate had higher PCMC perception scores than those who were less literate and unemployed. Respondents who rated their health as very good had higher PCMC perception scores than those who rated their health as poor. Female respondents who previously gave birth at a health facility had lower perceptions of dignity and respect than those with no prior facility birth.Conclusion: The findings imply that community perceptions of PCMC, particularly related to communication and autonomy, are poor. Given the effects of these perceptions on use of maternal health services, there is a need to improve PCMC.